Utilization and perception of intelligent tutoring systems among undergraduates in Ondo State, Nigeria - Ayelaagbe, Sina Opeoluwa (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study investigated the Intelligent Tutoring System (ITS) utilization and perception among undergraduates in Ondo State, Nigeria. A descriptive survey research design was used in the study respectively. Two research questions and one null hypothesis were answered and tested in the study. The sample size consisted of (620) undergraduates randomly sampled from the three (3) universities selected using a cluster sampling technique. (206) were selected from UNIMED, Ondo, from OASTEC Okitipupa (232) were selected and from AAU, Akungba, (192) were selected. The instrument for data collection was the researcher's self-developed questionnaire titled: "Intelligent Tutoring System Utilization and Perception Questionnaire (ITSUPQ)". The instrument was validated by three experts. The reliability coefficient of 0.70 for perception and 0.78 for usage of ITS for learning. Research questions were answered using mean and standard deviation, while the hypothesis was tested using ANOVA. The finding of the study showed that undergraduates perceived the usage of ITS and they also derived maximum benefits from the usage of ITS for learning. It was also revealed that there was no significant difference in the perceived usage of ITS by undergraduates based on area of specialization. The study therefore recommends that stakeholders in education should provide ITS infrastructural facilities to universities and undergraduates and lecturers should be trained towards the usage of the Intelligent Tutoring System (ITS).